2021
DOI: 10.3390/cells10061287
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles from Mesenchymal Stem Cells as Potential Treatments for Osteoarthritis

Abstract: Osteoarthritis (OA) is a chronic degenerative disorder of the joint and its prevalence and severity is increasing owing to ageing of the population. Osteoarthritis is characterized by the degradation of articular cartilage and remodeling of the underlying bone. There is little understanding of the cellular and molecular processes involved in pathophysiology of OA. Currently the treatment for OA is limited to painkillers and anti-inflammatory drugs, which only treat the symptoms. Some patients may also undergo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 140 publications
0
17
0
Order By: Relevance
“…EV transfer of miRNA has been extensively researched during the past decade. In particular, MSCs isolated from diverse sources (bone marrow, synovial membrane, adipose tissue, umbilical cord and embryonic cells) were reported to be able to transduce miRNA effects through secretion of EVs [37][38][39], mainly through leading to immunomodulation. Here, we demonstrated that chondrocytes also secrete miRNA through EVs and that the content of the EVs can be controlled by the expression of the miRNA.…”
Section: Discussionmentioning
confidence: 99%
“…EV transfer of miRNA has been extensively researched during the past decade. In particular, MSCs isolated from diverse sources (bone marrow, synovial membrane, adipose tissue, umbilical cord and embryonic cells) were reported to be able to transduce miRNA effects through secretion of EVs [37][38][39], mainly through leading to immunomodulation. Here, we demonstrated that chondrocytes also secrete miRNA through EVs and that the content of the EVs can be controlled by the expression of the miRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Exosomes have been shown to have favorable effects in a significant number of experiments conducted over the last decade. Compared to the MSCs, MSC-derived exosomes not only play an indispensable role in tissue repair and regeneration but also have a more lasting, potent, and “easier-to-preserve” role ( Mohd Noor et al, 2021 ). Owing to their small size, MSC-derived exosomes have greater stability and mitigate the risks associated with the administration of live cells, such as the possibility of microvascular blockage throughout the body.…”
Section: The Therapeutic Promise Of Exosomes Generated From Mscs In a Variety Of Tissuesmentioning
confidence: 99%
“…However, this hypothesis was later challenged by the findings from numerous studies in the last decade. There exists a consensus that MSCs exert their therapeutic functions in vivo mostly via the paracrine process, such as the release of signaling molecules including growth factors, cytokines, and extracellular vesicles ( Fayazi et al, 2021 ; Mohd Noor et al, 2021 ). Among them, exosomes, as the main transmission medium for intercellular communication, participate in a variety of pathological and physiological functions by means of influencing the gene expression, migration, proliferation, apoptosis, and metabolism in the recipient cells ( Pourakbari et al, 2019 ; Shi et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The application of autologous mesenchymal stem cells (MSCs) [ 4 ] may serve as an alternative therapeutic approach to the restoration of the cartilage tissue. The MSCs are multicomponent cells capable of differentiating into various types of cells, including chondrocytes, which allows us to use them in the process of creating cartilage-like structures as substitutes for damaged areas [ 5 , 6 ]. On the other hand, the therapeutic effect of the MSCs is based on paracrine secretion of a broad repertoire of growth factors and cytokines, which stimulate the proliferation of chondrocytes and the synthesis of the extracellular matrix (ECM) when injected into the joint [ 7 ].…”
Section: Introductionmentioning
confidence: 99%